Visual messages in art galleries (Journal of the College of Basic Education, 2022)
Human thought may operate according to an ideology that does not recognize the scientific logical boundaries that separate the times in their historical sequence, as it unites them with civilizational logic with the inclusiveness of the successive establishment of the unity of creative synthesis, to find the rhythm of communication that carries the message of human existence. There is no doubt that this human ability to adapt carried the secret of his creativity, and unified human action and behavior sometimes despite the difference in its parts or intellectual growth.